Performance patterns and records in the world aquatics masters championships: Where do the most frequently represented nations among the top-ten masters swimmers come from? - Sascha Moreitz; Wais Ahmad; Matthias Wilhelm; Aldo Seffrin; Marilia Santos Andrade; Pedro Forte; Arkadiusz Stanula; Lee Hill; Pantelis T. Nikolaidis; Katja Weiss; Thomas Rosemann; Beat Knechtle (PLoS ONE, 2026)
Background Masters Swimming is a rapidly expanding sector of competitive aquatic sport and provides structured opportunities for adults to maintain long-term engagement in high-level swimming. Despite extensive global participation, limited evidence exists regarding the national origins of the most frequent Masters swimmers among the top-ten performers across all strokes, distances, and age groups. Previous research has focused primarily on isolated disciplines or open-water events. This study aimed to investigate participation and performance patterns of Masters swimmers competing at the World Masters and World Aquatics Championships from 1986 to 2024, with a specific focus on national patterns among top performers. Methods A total of 204,005 long-course (50 m) swimming performance entries (94,312 women and 109,693 men) from 1986 to 2024 were extracted from the official World Aquatics archive and analyzed. The unit of analysis was the annual top-ten entries for each stroke, distance, sex, and age group, with each result treated as an independent performance record. Statistical differences between nationalities were assessed using Kruskal-Wallis tests with Bonferroni post-hoc adjustments. Descriptive data were presented using mean, standard deviation, and confidence intervals. Success was operationally defined as the frequency of a nation’s appearances in the annual top-ten fastest times for each stroke, distance, and sex. For descriptive purposes, nationalities were grouped into six categories: the top-five nationalities with the most appearances in the top-ten fastest times regarding the different swimming strokes and sex separately by distances and for each competition year, as well as one group of all other nationalities. Results Among women, German swimmers were the most numerous in the top-ten for breaststroke, butterfly, and 50 m backstroke. Among men, however, U.S. swimmers were the most frequently represented across almost all distances and strokes, except for the successes of Brazilian athletes in the 50 m backstroke and Russian swimmers in the 50 m breaststroke. Across all years and disciplines, the most recurrent top-ten Masters swimmers came from the USA, Germany, Great Britain, Russia, Italy, and Brazil (“Big Six”). Performance differences between nationalities were significant across multiple events, with notable strengths among Russian swimmers in breaststroke and freestyle sprint events. Conclusions The United States demonstrated the broadest and most consistent numerical superiority in Masters swimming performance over the 38-year period, by fielding the most frequent athletes among the top-ten performers, particularly among men. German women displayed exceptional success in breaststroke and butterfly, accounting for the majority of the athletes in the top-ten. These findings highlight persistent geographic patterns in Masters swimming excellence and may guide future research on environmental, sociocultural, training, and demographic factors contributing to national performance patterns.